Pemberdayaan Masyarakat Nelayan Pantai Padang Melalui Pemanfaatan Media Sosial Dalam Memasarkan Hasil Tangkapan Keluar Daerah - Annisa Raudah; Dhiva Nadya Maharani; Muhammad Surya Imam; Yulia Hanoselina; Rahmadhona Fitri Helmi (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study examines how traditional fishermen in Padang Coastal Area, West Sumatra, utilize social media to expand their market reach and improve economic welfare. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation with three fishermen who have adopted digital platforms such as WhatsApp, Facebook, and TikTok for marketing. The findings reveal that social media enables fishermen to bypass middlemen, establish direct consumer relationships, and implement pre-order systems, leading to higher profits and market stability. Key strategies include visual content marketing (e.g., real-time stories, videos) and personalized communication via WhatsApp. Despite generational gaps in digital literacy, younger fishermen exhibit greater adaptability to newer platforms like TikTok. The study highlights social media's role not only as a marketing tool but also as a catalyst for structural economic transformation, fostering trust, sustainability, and community-based digital ecosystems. Challenges include uneven digital access and the need for institutional support to strengthen infrastructure and skills. This research contributes to the discourse on digital empowerment in traditional sectors, offering insights for policymakers and stakeholders to enhance inclusive digital fisheries economies.